Handbook of adolescent psychology - Lerner, Richard M.; Steinberg, Laurence D., 1952- (Hoboken, NJ : John Wiley & Sons, 2009)
This multidisciplinary handbook, edited by the premier scholars in the field, reflects the empirical work and growth in the field of adolescent psychology.
v. 2. Contextual Influences on Adolescent Development. pt. 1. Interpersonal influences: Parent-child relationships during adolescence / Brett Laursen and W. Andrew Collins ; Adolescents' relationships with siblings / Patricia L. East ; Peer relationships in adolescence / B. Bradford Brown and James Larson ; Romantic relationships in adolescence / Jennifer A. Connolly and Caroline McIsaac ; Mentoring in adolescence / Jean E. Rhodes and Sarah R. Lowe -- pt. 2. Institutional Influences: Schooling adolescents / Richard F. Elmore ; Adolescent out-of-school activities / Joseph L. Mahoney [and others] ; Adolescents and the world of work / Jeremy Staff, Emily E. Messersmith, and John E. Schulenberg ; Adolescence, adolescents, and media / Donald F. Roberts, Lisa Henriksen, and Ulla G. Foehr ; The legal regulation of adolescence / Jennifer L. Woolard and Elizabeth Scott ; The development of citizenship / Lonnie R. Sherrod and James Lauckhardt -- pt. 3. The Broader Context of Adolescence: Neighborhood influences on adolescent development / t
Includes bibliographical references and indexes.
Includes bibliographical references and index.
Keywords: Adolescent psychology; Adolescent psychology -- Handbooks; Adolescent psychiatry -- Handbooks; Adolescent psychology